Exposure to Glycolytic Carbon Sources Reveals a Novel Layer of Regulation for the MalT Regulon - Sylvia A. Reimann; Alan J. Wolfe (International Journal of Microbiology)
Bacteria adapt to changing environments by means of tightly coordinated regulatory circuits. The use of synthetic lethality, a genetic phenomenon in which the combination of two nonlethal mutations causes cell death, facilitates identification and study of such circuitry. In this study, we show that the E. coli ompR malTcon double mutant exhibits a synthetic lethal phenotype that is environmentally conditional. MalTcon, the constitutively active form of the maltose system regulator MalT, causes elevated expression of the outer membrane porin LamB, which leads to death in the absence of the osmoregulator OmpR. However, the presence and metabolism of glycolytic carbon sources, such as sorbitol, promotes viability and unveils a novel layer of regulation within the complex circuitry that controls maltose transport and metabolism.